The emergence of workers’ power in sugar mills: advances, limitations and questions. Tucumán, 1944-1949 (Quinto Sol, 2014)
During the first decade of Peronism workers interpellated the almost omnipresent authority of the employers in factories and boosted a transferof power that challenged the power of industrialists on decisions so far considered exclusive: the administration and organization of the workforceand the control of production processes. In the case of sugar mills from Tucuman, strikes to demand the dismissal of certain referents of the factory hierarchy and institutionalization of seniority became two key aspects of this redistribution of power. These instances -related to recruitment, promotion and dismissal of staff- interpellated businessmen who tried to resist the advance of workers, but they also confronted the Peronist government with its limit of acceptability, prompting it to control the amount of workers’ power.
Keywords: sugar unionism; workers’ power; industrial businessmen; peronism; Tucumán